Diagnosing clinical malnutrition: Perspectives from the past and implications for the future. (August 2018) - Teigen, Levi M.; Kuchnia, Adam J.; Nagel, Emily M.; Price, Kathleen L.; Hurt, Ryan T.; Earthman, Carrie P.
Summary: This review, intended for both researchers and clinicians, provides a history of the definition of clinical malnutrition. Despite global efforts, we remain without one clear, objective, internationally accepted definition; clarity in this regard will ultimately improve our evaluation and monitoring of nutritional status to achieve optimal patient outcomes. In this review we explore the development of the term malnutrition and its diagnosis and application in the setting of acute and chronic disease. We begin in the second century A.D. with the work of the Greek physician Galen who is credited as the first to apply the term marasmus to characterize three categories of malnutrition, which are surprisingly similar to components of current international definitions. We then highlight significant developments over the next 2000 years culminating in our current application of the clinical diagnosis of malnutrition. A perspective on historical practices may inform current efforts toward a global definition and diagnosis of malnutrition.